The republican exile and the return through digital and audiovisual media. Lidia Bocanegra Barbecho, Sandra Haro Márquez, Yolanda Guasch Marí, Guiomar Acevedo López (Coordinators). An Introduction - Bocanegra Barbecho, Lidia; Haro Márquez, Sandra; Guasch Marí, Yolanda; Acevedo López, Guiomar (Hispania Nova, 2021)
This text introduces the papers that structure the Dossier “The Republican Exile and the Return through Digital and Audiovisual Media”, and focuses on analyzing all the issues and advances regarding to the study of the Republican exile and the return, from a digital perspective. Archives, databases, digital sources and e-projects are the key elements around which the analysis of the different papers, from the Digital History and Digital Humanities fields, revolve.